2014
DOI: 10.1002/chem.201303913
|View full text |Cite
|
Sign up to set email alerts
|

A Small Change in Central Linker Has a Profound Effect in Inducing Columnar Phases of Triazine‐Based Unconventional Dendrimers

Abstract: Four unconventional triazine-based dendrimers have been prepared and characterized by (1) H and (13) C NMR spectroscopies, mass spectrometry, and elemental analysis. Based on DSC studies, polarizing microscopy, and powder XRD, two of these dendrimers, containing linkers with an odd number of carbon atoms, were observed to display columnar liquid-crystalline phases during thermal treatment. However, the other two dendritic analogues, containing linkers with an even number of carbon atoms, were not observed to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 91 publications
1
18
0
Order By: Relevance
“…Molecular weights for dendrimers 9-12 are similar: ~6050, ~603 respectively. A computer simulation for molecular conformations of showed that 9 is asymmetrical and 10 is symmetrical along with the c diagram can show their differences [63]. As shown in Figure 6, den carbon linker in the dendritic core, allows the dendronic halves to b Molecular weights for dendrimers 9-12 are similar:~6050,~6036,~6022, and~6008, respectively.…”
Section: Lc Dendrimers With the Loss Of C 2 Symmetry By Changing The Central Coresmentioning
confidence: 96%
See 3 more Smart Citations
“…Molecular weights for dendrimers 9-12 are similar: ~6050, ~603 respectively. A computer simulation for molecular conformations of showed that 9 is asymmetrical and 10 is symmetrical along with the c diagram can show their differences [63]. As shown in Figure 6, den carbon linker in the dendritic core, allows the dendronic halves to b Molecular weights for dendrimers 9-12 are similar:~6050,~6036,~6022, and~6008, respectively.…”
Section: Lc Dendrimers With the Loss Of C 2 Symmetry By Changing The Central Coresmentioning
confidence: 96%
“…This strategy can also be applied to central linkers of dendrimers. With the peripheral group fixed by the dialkylamino units, the central linker is modulated as C 5 H 10 , C 4 H 8 , C 3 H 6 , and C 2 H 4 ( Figure 5 ) [ 63 ]. Dendrimers 9 and 11 , with the odd-number carbon linker in the dendritic core, are LCs.…”
Section: Formation Of Triazine-based Lc Dendrimers By Manipulating Their Molecular Morphologymentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, nanophase segregation of distinct segments within the molecules having dendritic structural features hold a promise . Studies of the order and complexity, leading to distinct mesophase structures, were studied systematically using preformed dendrimers by modifying the peripheries with chosen mesogenic moieties . Elegant examples are (i) amphiphilic ionic second generation poly(amido amine) (PAMAM) dendrimer functionalized with differing amounts of myristic acid that exhibit a smectic A mesophase; (ii) second‐generation poly(propyleneimine) dendrimers peripherally functionalized with 4‐methoxybiphenyl, 4‐methoxyphenyl benzoate, trans ‐4‐(4‐pentylcyclohexyl)phenyl, 4‐fluorobiphenyl, and 3,4,5‐trifluorobiphenyl that exhibit a spontaneous homeotropic arrangement and (iii) azobenzene‐functionalized carbosilane dendrimers of first to fourth generations that prefers a smectic layer arrangement, whereas the fifth generation dendrimer of the same series prefers a rectangular columnar arrangement …”
Section: Introductionmentioning
confidence: 99%